규칙적인 생식섭취가 고지혈증 환자의 영양소 섭취상태, 체지방 및 혈청의 지질조성에 미치는 영향 - 한종현(Han Jong Hyun); 박성혜(Park Sung Hye) (Hanʼguk yongyang hakhoe chi, 2003)
This study was designed to investigate the effects of weight reduction and changes in serum lipid composition using a commercial uncooked powdered food (UPF) diet on 27 obese hyperlipidemic women over a period of 12 weeks. We replaced the standard breakfast and dinner of each of the subjects with UPF. Their dietary intake status was evaluated by 24-hour recall method. Their body compositions were measured using a body fat analyzer. Also, we conducted hematological, clinical and lipid profile analyses of their blood. Their intake of energy, lipid and protein significantly decreased as the subjects started to take UPF, but their intake of vitamins and minerals, other than iron, increased. Due to the energy intake decrease, the subjects' weight, body fat and waist circumference significantly decreased. Among the lost weight the percentage of the body fat was high. We judged that this process of losing weight was successful in obese hyperlipidemic women. Serum HDL-cholesterol gradually increased and serum total-cholesterol, LDL-cholesterol, triglyceride levels showed gradual decreases. When obese hyperlipidemic women replaced two of three meals with UPF for 3 months, we were able to see useful changes like decreased body fat and serum lipid. Complete judgment on the usefulness of UPF may be difficult but if people take a standard meal once a day and replenish their iron by taking UPF twice a day, we assume that replacing UPF with balanced regular meal not be a problem in nutritional status. Our results show that UPF is effective in the diet therapy of obese hyperlipidemic women.